Signifikasi Peran Parpol dalam Pembangunan Menuju Terciptanya Masyarakat Madani Era Reformasi - Friska Ayu Anggraini; Siti Fatimah (CV. Creative Tugu Pena, 2024)
The role of political parties (Parpol) in development towards the creation of civil society is an interesting and complex aspect in the political dynamics of a country. Civil society is a concept that embodies the ideals of a social order that is democratic, just and has a humanitarian perspective. In this context, the role of political parties has a significance that cannot be ignored. This research aims to explore various dimensions of the role of political parties in civil society development, as well as their implications for socio-political transformation in a country. The research method used is literature analysis and a qualitative approach to explore a deeper understanding regarding this phenomenon. The research results show that the role of political parties in civil society development has a very important dimension. First, political parties act as a forum for political representation of society, connecting people's interests with the process of making public policies. Second, political parties have the responsibility to build political awareness and public participation in the democratic process, form a critical mindset, and educate the public about their rights and obligations in the state. Third, political parties play a role in government supervision and accountability, ensuring transparency and fairness in government administration. However, the role of political parties in civil society development also faces a number of challenges. Among them are the practices of corruption and nepotism within the party which damage its image and integrity, as well as the entanglement of political parties in power dynamics which often leads to political polarization and social conflict. In conclusion, the role of political parties in developing civil society is a crucial factor in determining the direction and success of a country in achieving democratic and just ideals. Therefore, real efforts are needed to strengthen the role of political parties as development agents that are responsible, transparent and oriented towards the interests of the people, so that they are able to create a prosperous and civilized civil society.